Oral creatine supplementation and skeletal muscle metabolism in physical exercise - Mesa, J. L.; Ruiz, J. R.; Gonzalez-Gross, M. M.; Gutierrez Sainz, A.; Castillo Garzon, M. J. (Sports Medicine, 2002)
Creatine is the object of growing interest in the scientific literature. This is because of the widespread use of creatine by athletes, on the one hand, and to some promising results regarding its therapeutic potential in neuromuscular disease on the other. In fact, since the late 1900s, many studies have examined the effects of creatine supplementation on exercise performance. This article reviews the literature on creatine supplementation as an ergogenic aid, including some basic aspects relating to its metabolism, pharmacokinetics and side effects. The use of creatine supplements to increase muscle creatine content above ~20 mmol/kg dry muscle mass leads to improvements in high-intensity, intermittent high-intensity and even endurance exercise (mainly in nonweightbearing endurance activities). An effective supplementation scheme is a dosage of 20 g/day for 4-6 days, and 5 g/day thereafter. Based on recent pharmacokinetic data, new regimens of creatine supplementation could be used. Although there are opinion statements suggesting that creatine supplementation may be implicated in carcinogenesis, data to prove this effect are lacking, and indeed, several studies showing anticarcinogenic effects of creatine and its analogues have been published. There is a shortage of scientific evidence concerning the adverse effects following creatine supplementation in healthy individuals even with long-term dosage. Therefore, creatine may be considered as a widespread, effective and safe ergogenic aid.